2010
DOI: 10.1002/chem.200901668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystallochromy of 1,4,7,10‐Tetraalkyltetracenes: Tuning of Solid‐State Optical Properties of Tetracenes by Alkyl Side‐Chain Length

Abstract: We synthesized a series of 1,4,7,10-tetraalkyltetracenes using a new 2,6-naphthodiyne precursor and 2,5-dialkylfurans as starting materials (alkyl=methyl to hexyl). Surprisingly, the solid-state color of the tetracenes ranges through yellow, orange, and red. Both yellow and red solids are obtained for the butyl derivative. Optical properties in solution show no marked differences; however, those in the solid state show characteristics that vary with alkyl side-chain length: methyl, propyl, and pentyl derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…In this paper, one will focus on the six most representative families of compounds displaying color polymorphism, whose most famous members are represented in Fig. 2: N-(4-methyl-2-nitrophenyl) acetamide [20][21][22][23][24][25][26] , dimethyl 2,5-dichloro-3,6-dihydroxyterephthalate [27][28][29][30][31][32][33][34][35] , 5-methyl-2-((2-nitrophenyl)amino)thiophene-3-carbonitrile (ROY) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] , 2,4,6-trinitro-N-(p-tolyl)aniline [54][55][56][57][58][59][60][61] , dimethyl-5-benzoyl-3-phenylindolizine-1,2-dicarboxylate 14 , and 1,4,7,10-tetrabutyltetracene [62][63][64] .…”
mentioning
confidence: 99%
“…In this paper, one will focus on the six most representative families of compounds displaying color polymorphism, whose most famous members are represented in Fig. 2: N-(4-methyl-2-nitrophenyl) acetamide [20][21][22][23][24][25][26] , dimethyl 2,5-dichloro-3,6-dihydroxyterephthalate [27][28][29][30][31][32][33][34][35] , 5-methyl-2-((2-nitrophenyl)amino)thiophene-3-carbonitrile (ROY) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] , 2,4,6-trinitro-N-(p-tolyl)aniline [54][55][56][57][58][59][60][61] , dimethyl-5-benzoyl-3-phenylindolizine-1,2-dicarboxylate 14 , and 1,4,7,10-tetrabutyltetracene [62][63][64] .…”
mentioning
confidence: 99%
“…DFT calculations on the B3LYP/6‐31G** level, as similarly applied by others in related studies,20e, 35a revealed that the tristetracenes 9 and 10 have their highest occupied molecular orbitals (HOMOs; A 2 symmetry) and lowest occupied molecular orbitals (LUMOs; A 1 ) spread about the whole C 3 v ‐symmetrical molecular framework (see the Supporting Information) 36. Compared with 9 , the energies of the occupied MOs of 10 are slightly increased, whereas the increase of the LUMO energies is negligible.…”
Section: Resultsmentioning
confidence: 73%
“…Kitamura et al. reported that, in the solid state, the UV/Vis spectra of 1,4,7,10‐tetraalkyltetracenes strongly depended on the length of the alkyl substituents . Similarly, UV/Vis and fluorescence spectral changes by varying the alkyl chain lengths have been reported for a number of π‐conjugated systems .…”
Section: Introductionmentioning
confidence: 94%
“…[7][8][9] Kitamura et al reported that, in the solid state, the UV/Vis spectrao f 1,4,7,10-tetraalkyltetracenes strongly dependedo nt he length of the alkyl substituents. [10] Similarly,U V/Vis and fluorescence spectralc hanges by varying the alkyl chain lengths have been reportedf or an umber of p-conjugated systems. [11] Konishi et al prepared pyrene derivatives with mono-to tetraalkyl substituents and investigated their photophysical properties, demonstrating the alkyl substituent effects on the pyrene chromophores,b ut the solid-state photophysical properties were not examined.…”
Section: Introductionmentioning
confidence: 99%